STRATEGI KOMUNIKASI PEMASARAN RADIO DUIS FM INDRAGIRI HULU DALAM MENINGKATKAN JUMLAH PENGIKLAN - Kariem, : Muhammad Syukron Amien Abdul; Lubis, Evawani Elysa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Each radio performs various strategiesto improve the rating listenercan survive in industrial competitionwhich is growing. Radio workers must do the strategyand action to attract attentionlistener so that the number of advertisers will be interested to advertise.The success of a radio and its riseThe success of a radio and the increasing number of advertisers, certainly not separated from a good marketing communication strategy. This is very influential on the success of radio marketing is soaring rapidly. Therefore, many companies are struggling in the business world trying hard to survive. For that it takes a marketing communication strategy that can convey the message effectively and on target so that the company is not left by the audience. The design used in this research is qualitative with descriptive approach. The design of this study describes and describes the state of the subject and object of research. Key informants in this study were Radio Duis FM Indragiri upstream managers and advertisers with an advertiser category of longer or more than one year and a category of new advertisers or less than 1 year. The total resource in this research is 5 people. Data collection techniques used are observation, interview and documentation. In achieving the validity of the data in this study, the authors use extension of participation and triangulation. The results of this study indicate that the process of marketing communication strategy Duis FM radio is done that is with an interesting program to hold quizzes with prizes to attract attention, grow the interest of advertisers and make decisions to put an ad, this is also called Pull Strategy. The Push Strategy used Duis FM radio in increasing the number of advertisers using interpersonal media to increase the loyalty of prospective advertisers as well as attract new advertisers directly to influence the psychological goals. Strategies using social media are useful for interacting and maintaining a broad and up to date relationship with listeners and advertisers. Likewise with the Pass Strategy used Duis FM radio in increasing the number of advertisers is to hold an event where the goal to be closer to the community by way of present in the community to provide information, cause intention and make decisions to put an ad. Keyword : Marketing communication strategy Duis FM Indragiri Hulu